Non‐Thermal Plasma in Contact with Water: The Origin of Species. Issue 10 (2nd February 2016) - Gorbanev, Yury; O'Connell, Deborah; Chechik, Victor
Abstract: Non‐thermal atmospheric pressure plasma has attracted considerable attention in recent years due to its potential for biomedical applications. Determining the mechanism of the formation of reactive species in liquid treated with plasma is thus of paramount importance for both fundamental and applied research. In this work, the origin of reactive species in plasma‐treated aqueous solutions was investigated by using spin‐trapping, hydrogen and oxygen isotopic labelling and electron paramagnetic resonance (EPR) spectroscopy. The species originating from molecules in the liquid phase and those introduced with the feed gas were differentiated by EPR and 1 H NMR analysis of liquid samples. The effects of water vapour and oxygen admixtures in the feed gas were investigated. All the reactive species detected in the liquid samples were shown to be formed largely in the plasma gas phase. It is suggested that hydrogen peroxide (determined by UV/Vis analysis) is formed primarily in the plasma tube, whereas the radical species ⋅OOH, ⋅OH and ⋅H are proposed to originate from the region between the plasma nozzle and the liquid sample. Abstract : Cool plasma ! The source of reactive oxygen species induced by non‐thermal plasma in water has been investigated by UV, EPR and 1 H NMR spectroscopy and MS in conjunction with the use of isotopically labelled water. The main regions in which species are formed are identified (see picture). An understanding of the fundamental properties of plasma is of paramount importance in applied biomedical plasma research.